Implementing a Mobile Application News Tool for Disseminating Messages and Events of AlBuraimi University College - ALFarsi, Ghalia Musallam; Jabbar, Jasiya; ALSinani, Maryam (International Journal of Interactive Mobile Technologies (iJIM), 2018)
Technology is developing and changing in every moment that all domains are patchy without it. Our research utilizes the current trends and technology to design and develop a mobile application for the all members of the college. The students are the fundamental members in the college and they are our targets. Mobile notification system is an emerging technology, which influence in solving various dimensions of life. The college announcements and events are disseminated to students and staff through circulars, notice boards, emails, etc. Our research was to employ mobile affinity of especially students who ignore the circulars and notifications in notice board. The tool may be installed from play store mobile. The tool supports the widely used mobile operating system like android and iphone. This tool helps and provides a flexible way for communication. It list all events and news at AlBuraimi University College (BUC) like announcement of training courses and scientific workshop or classes cancel and others events. It also helps in easy access of college portal for both students and staff. The evaluation held finds positive response towards the need of this mobile application. The result shows the interest and satisfaction of users with BUC NEWS mobile application tool